NILAI LOKAL JOU SE NGOFANGARE SEBAGAI BASIS KERUKUNAN MAS YARAKAT TERNATE, MALUKU UTARA - la sakka (Al-Qalam, 2007)
This research was conducted in Ternate, North Maluku. This researchaims to describe the local value jou se ngofangare as basic on socialconstruction in Ternate society. This uses qualitative method, wheredata was collected by depth interview. Then, data was analyzed bydescriptive qualitative.This research indicates that this jou se ngofangare consists severalprinciples are: adat se torang (regulation of social relation), galib selakudi (power distribution), sere se duniru (regulation of God), cing secingare (God supervision), bobaso se rasai (care to other man suffering),cara se ngale (God way), loa se banar (right act), and bari (workingtogether). This local value is very important in maintaining thesocial relation among Ternate people that very plurals